Emission of CO2 and CH4 from a multi-ditches system in rice cultivation region: Flux, temporal-spatial variation and effect factors. (15th September 2020) - Deng, Ouping; Li, Xi; Deng, Liangji; Zhang, Shirong; Gao, Xuesong; Lan, Ting; Zhou, Wei; Tian, Dong; Xiao, Yinlong; Yang, Juan; Ou, Dinghua; Luo, Ling
Abstract: Man-made multi-level ditches system is designed to irrigate, drain and collect runoff from surrounding fields. It is not only the conduit of water and field carbon, but also the linear-like wetland with complex carbon cycling. However, the contribution of ditches system to CO2 and CH4 emission has rarely been assessed. To understand the emission pattern of CO2 and CH4 from ditches, this study investigated the emission fluxes of CO2 and CH4 in a three-level ditches system in Chengdu Plain, China. The results showed that the emission of CO2 and CH4 ranged from 70.38 to 950.40 mg C m −2 h −1 and 6.51–74.99 mg C m −2 h −1, respectively, and was higher in spring and summer than other seasons in all ditches ( P  < 0.05). On the other hand, the emission of CO2 and CH4 increased along with the decreasing ditches size. Besides, it is found that the precipitation, water table depth and water DO concentration might contribute to the emission of CO2, while CH4 was possibly influenced by precipitation, water table depth, temperature, water DO and DOC concentration. Moreover, it is suggested that terrestrial external input and in-situ metabolism might be the main sources of C emission, and in-situ source might largely contribute to CH4 emission. To reduce the C emission, it is necessary to improve fertilization and irrigation methods, limit soil pollutants transferring into ditches, and frequently dredge sediments in future. Highlights: The emission of CO2 and CH4 increased with decreasing ditches size. Terrestrial external input and in-situ metabolism might affect ditch C emission. In-situ source might largely contribute to CH4 emission.